Linear Graph Intersection

Algebra Level 3

f ( x ) f(x) is a linear function with the term f ( x ) f(x) = a x + b ax + b .

f ( x ) f(x) = a x + b ax + b

Then we define another two function, g ( x ) g(x) and h ( x ) h(x) .

g ( x ) g(x) = f ( f ( x ) ) f(f(x))

h ( x ) h(x) = f ( f ( f ( x ) ) ) f(f(f(x)))

When drawn on a Cartesian Coordinate, f ( x ) f(x) and g ( x ) g(x) intersect at point M M , f ( x ) f(x) and h ( x ) h(x) intersect at point N N , and g ( x ) g(x) and h ( x ) h(x) intersect at point P P .

If f ( x ) f(x) , g ( x ) g(x) , and h ( x ) h(x) are all non-coincident and non-parallel, which of the following statement is true?

None of the above are true. M M , N N , and P P creates an equilateral triangle. M M , N N , and P P are the same point. M M , N N , and P P creates an isoceles triangle.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chris Lewis
Aug 25, 2020

If a = 1 a=1 , then the three lines y = f ( x ) y=f(x) , y = g ( x ) y=g(x) , y = h ( x ) y=h(x) are parallel (or coincide).

If a 1 a \neq 1 , then f f has a unique fixed point (the intersection of the lines y = x y=x and y = f ( x ) y=f(x) ). Say this point is t t , that is f ( t ) = t f(t)=t .

Now it's easy to see that t t is also a fixed point of g g and h h ; so all three lines pass through the point ( t , t ) (t,t) .

Since y = g ( x ) y=g(x) and y = h ( x ) y=h(x) are also straight lines, this point of intersection must be unique; ie M , N , P M,N,P are all the same point.

Never think like this before. Great solution!

David Saing - 9 months, 1 week ago
David Saing
Aug 23, 2020

f ( x ) f(x) = a x + b ax + b

g ( x ) g(x) = f ( f ( x ) ) f(f(x))

h ( x ) h(x) = f ( f ( f ( x ) ) ) f(f(f(x)))

First, let's find the coordinate of point M M in general. At point M M , the x x value and the y y value of point M M satisfies both f ( x ) f(x) and g ( x ) g(x) . So, we can equalize both functions to find the value of x x that satisfies both functions.

f ( x ) f(x) = g ( x ) g(x)

a x + b ax + b = f ( a x + b ) f(ax + b)

a x + b ax + b = a × ( a x + b ) + b a \times (ax + b) + b

a x ax = a × ( a x + b ) a \times (ax + b)

We divide both sides by a a

x x = a x + b ax + b

x a x x - ax = b b

x × ( 1 a ) x \times (1 - a) = b b

x x = b 1 a \frac{b}{1-a}

Now substitute the x x value to any function to find the y y value. This time let's choose the function f ( x ) f(x) .

y y = a x + b ax + b

y y = a × b 1 a + b a \times \frac{b}{1-a} + b

y y = a b 1 a + b × ( 1 a ) 1 a \frac{ab}{1-a} + \frac{b \times (1-a)}{1-a}

y y = a b + b a b 1 a \frac{ab + b - ab}{1-a}

y y = b 1 a \frac{b}{1-a}

So, in general, point M M has the coordinate ( b 1 a \frac{b}{1-a} , b 1 a \frac{b}{1-a} ).

Next, let's find the coordinate of point N N in general. At point N N , the x x value and the y y value of point N N satisfies both f ( x ) f(x) and h ( x ) h(x) .

f ( x ) f(x) = h ( x ) h(x)

a x + b ax + b = f ( f ( f ( x ) ) ) f(f(f(x)))

a x + b ax + b = f ( g ( x ) ) f(g(x)) (because g ( x ) g(x) = f ( f ( x ) ) f(f(x))

a x + b ax + b = f ( a × ( a x + b ) + b ) f( a \times (ax + b) + b)

a x + b ax + b = a × ( a 2 x + a b + b ) + b a \times ( a^{2}x + ab + b ) + b

a x ax = a × ( a 2 x + a b + b ) a \times (a^{2}x + ab + b)

We divide both sides by a a

x x = a 2 x + a b + b a^{2}x + ab + b

x a 2 x x - a^{2}x = a b + b ab + b

x × ( 1 a 2 ) x \times (1 - a^2) = b × ( a + 1 ) b \times ( a + 1 )

x × ( 1 + a ) ( 1 a ) x \times (1 + a)(1 - a) = b × ( 1 + a ) b \times (1 + a)

x × ( 1 a ) x \times (1 - a) = b b

x x = b 1 a \frac{b}{1-a}

Now substitute the x x value to any functions to find the y y value. This time let's choose the function h ( x ) h(x) .

y y = a × ( a 2 x + a b + b ) + b a \times ( a^{2}x + ab + b ) + b

y y = a 3 x + a 2 b + a b + b a^{3}x + a^{2}b + ab + b

y y = a 3 × b 1 a + a 2 b + a b + b a^{3} \times \frac{b}{1-a} + a^{2}b + ab + b

y y = a 3 b 1 a + a 2 b × ( 1 a ) 1 a + a b × ( 1 a ) 1 a + b × ( 1 a ) 1 a \frac{a^{3}b}{1-a} + \frac{ a^{2}b \times (1-a) }{1-a} + \frac{ ab \times (1-a) }{1-a} + \frac{b \times (1-a) }{1-a}

y y = a 3 b + a 2 b a 3 b + a b a 2 b + b a b 1 a \frac{ a^{3}b + a^{2}b - a^{3}b + ab - a^{2}b + b - ab }{1-a}

y y = b 1 a \frac{b}{1-a}

So, in general, the point N N has the coordinate ( b 1 a \frac{b}{1-a} , b 1 a \frac{b}{1-a} ).

Now that the intersection point of ' f ( x ) f(x) and g ( x ) g(x) ' and ' f ( x ) f(x) and h ( x ) h(x) )' is the same, it can't make a triangle since there are two points that coincide. because M M and N N are same, then P P must also be the same point, because if P P is not the same point, then the lines will intersect at three different points. Therefore, M M , N N , and P P are the same point.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...